The devil wears plaid - Medeiros, Teresa, 1962- (New York : Pocket Books, 2010)
About to speak wedding vows that will bind her to the elderly Earl of Hepburn and save her family from poverty, Emmaline Marlowe finds herself abducted by Hepburn's sworn enemy, Jamie Sinclair. Trapped in the Scottish wilds with Jamie and his men, she tries to unravel a tangled mystery around the source of the feud: the unsolved murder of Jamie's parents.
Keywords: Great Britain -- History -- 1800-1837 -- Fiction; Scotland -- History -- 19th century -- Fiction; Historical fiction; Love stories